AACSB Peer Review Team (PRT) visit 2024 - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
Arshad Ayub Graduate Business School (AAGBS) hosted the AACSB Peer Review Team (PRT) Visit 2024 from 13th October to 16th October as part of the School's journey towards obtaining Athe prestigious AACSB Accreditation. This final visit served as a crucial milestone in the School's continuous efforts to achieve academic excellence.